2019
DOI: 10.1186/s12936-019-2921-9
|View full text |Cite
|
Sign up to set email alerts
|

ELQ-331 as a prototype for extremely durable chemoprotection against malaria

Abstract: Background The potential benefits of long-acting injectable chemoprotection (LAI-C) against malaria have been recently recognized, prompting a call for suitable candidate drugs to help meet this need. On the basis of its known pharmacodynamic and pharmacokinetic profiles after oral dosing, ELQ-331, a prodrug of the parasite mitochondrial electron transport inhibitor ELQ-300, was selected for study of pharmacokinetics and efficacy as LAI-C in mice. Methods Four trials we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 31 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…ELQ‐331, an alkoxycarbonate ester of ELQ‐300, is currently the lead prodrug that is reported to have significantly increased ELQ‐300 exposure after oral dosing [140]. ELQ‐331 is currently advancing preclinical development as an oral formulation and is also being progressed as a long‐acting injectable chemoprotection agent [141].…”
Section: Development Of Second‐generation Plasmodium Falciparum Cyt Bmentioning
confidence: 99%
“…ELQ‐331, an alkoxycarbonate ester of ELQ‐300, is currently the lead prodrug that is reported to have significantly increased ELQ‐300 exposure after oral dosing [140]. ELQ‐331 is currently advancing preclinical development as an oral formulation and is also being progressed as a long‐acting injectable chemoprotection agent [141].…”
Section: Development Of Second‐generation Plasmodium Falciparum Cyt Bmentioning
confidence: 99%
“…A novel class of compounds, endochin-like quinolones (ELQs) has recently been reported with high potency against B. microti and B. duncani [11,57]. Previously reported for their high potency against other apicomplexan parasites such as Plasmodium [115][116][117][118][119][120][121][122][123][124][125], Toxoplasma [126,127] and Leishmania [128], ELQs have been shown to target the cytochrome bc 1 complex of the parasites (Figure 3) [117,120,122,[128][129][130]. In 2016, Lawres et al demonstrated potency of ELQ-271 and ELQ-316 in the short-term ex vivo culture system of B. microti as well as in the in vivo SCID model of B. microti infection.…”
Section: Novel Therapies Under Investigation For the Treatment Of Human Babesiosismentioning
confidence: 99%
“…ELQ-300 is also another drug being developed as a long-acting injectable chemo-protective agent. This parasiticidal drug is reported to inhibit cytochrome bc 1 complex of Plasmodium parasites and bypass resistant mutations to atovaquone [ 79 , 80 ].…”
Section: Ongoing Approaches To Tackle Drug-resistant Malariamentioning
confidence: 99%